A simple approach to understand the physical aging in polymers. (7th December 2018) - Minguez, Rikardo; Barrenetxea, Lander; Solaberrieta, Eneko; Lizundia, Erlantz
Abstract: Glassy-state structural relaxation is a physical phenomenon that occurs in most amorphous and semicrystalline polymers after their melt-processing. As such, after these industrial conformation processes, polymers are usually found in a thermodynamic non-equilibrium state. Therefore, polymer chains undergo thorough conformational changes on their way towards a thermodynamically stable state. These molecular-level events involve macroscopic-level modifications, which are manifested as changes in physical properties. Here we propose a simple approach to monitor the physical aging in polymers by differential scanning calorimetry (DSC). Accordingly, the β H enthalpy relaxation rate is directly extracted from the DSC curves taking into account the enthalpy loss at different aging times. This method allows a simple quantification of the bulk aging dynamics in polymers, and can be extrapolated to systems containing reinforcing particles; i.e. composites and nanocomposites. This safe, low cost and simple experiment designed for undergraduate students of physical, chemical and engineering specialities serves as a guide to easily determine the physical aging suffered by polymeric materials during their storage and to understand its implications at macroscopic level, which is a relevant field in condensed-matter physics. Given the paramount relevance of physical aging in glassy materials, this experiment may also serve to raise awareness of the importance of the thermal history of materials on their resulting properties, which is overlooked too often.